Correlation between Neutrophil-to-Lymphocyte Ratio and Pretreatment Magnetic Resonance Imaging and Their Predictive Significance in Cervical Carcinoma Patients Referred for Radiotherapy. (18th March 2022) - Liang, Chunyu; Xu, Zhiyuan; Shen, Xinping; Wu, Kusheng
Abstract : Objective . The aim of this study was to determine the correlation between neutrophil-to-lymphocyte ratio (NLR) and various tumor parameters assessed by pretreatment magnetic resonance imaging (MRI) and to evaluate their prognostic significance for cervical carcinoma treated with radiotherapy (RT). Methods . The study enrolled 78 patients with biopsy-proven squamous cell carcinoma (SCC) of primary cervical cancer (clinically staged IB2 to IVA) who were treated in the Department of Clinical Oncology of the University of Hong Kong-Shenzhen Hospital between August 2015 and May 2019. A retrospective analysis of patients with SCC was performed. Firstly, we investigated the correlations between NLR and MRI parameters. Then, univariate and multivariate analyses were performed to identify the prognostic factors for overall survival (OS) and progression-free survival (PFS). Kaplan–Meier curves were constructed for OS and PFS. Results . Higher NLR showed significant association with larger tumor diameter and parametrial invasion assessed by pretreatment MRI. Univariate analysis indicated that uterine body invasion, parametrial invasion, and NLR were associated with prognosis of cervical cancer. Multivariable analyses demonstrated that parametrial invasion and NLR higher than the cutoff were independently associated with shorter OS and PFS, whereas uterine body invasion showed a significantly unfavorable influence on OS but showed no significant effect on PFS. Using the three risk factors of NLR above cutoff, parametrial invasion, and uterine body invasion, patients were divided into three subgroups. The three-year OS rates of patients with zero risk factors, one risk factor, and two or three of these factors were 96%, 91%, and 42%, respectively (P < 0.001 ), showing a downward trend. Conclusions . Uterine body invasion, parametrial invasion, and NLR were significant prognostic factors for patients with cervical carcinoma treated with RT. These results may supplement FIGO staging to improve prognostic assessment of patients.